UNIVERSIDADE PÚBLICA, DEMOCRÁTICA E POPULAR: OS DESAFIOS DA IMPLANTAÇÃO DA UNIVERSIDADE FEDERAL DA FRONTEIRA SUL - Vicente de Paula Almeida Júnior (Universidade Federal de Santa Catarina, 2011)
This article aims to present the process of implementation of the Universidade Federal da Fronteira Sul from some of the conditions of its implementation (context lines), the outlined concept of a public, democratic and popular university (concept) and, finally, the constitution of its institutional organization, interstate and multicampi (institutional design). Thus, it demonstrates the importance of considering the environment as a key part in building policies and strategies of an institution that is born from the demands of the social movements. It aims to ensure access to public and quality higher education, professional qualifying and commitment to social inclusion and development of education, research and extension as a condition of existence of a critical, researcher and innovator teaching. UFFS seeks to build a different organizational structure, where the campi are the basic organs and are considered equally important, ensuring the same quality standard for the conditions of physical and human infrastructure within each campus. The essence is to maintain constant dialogue between the administrative, regulatory and educational instances, among the superior and basic organs of the university, where the administrative and pedagogical autonomy takes place in all university campi.